Discrepancies in bioassay and chromatography determinations explained by metabolism of itraconazole to hydroxyitraconazole: studies of interpatient variations in concentrations. - Hostetler, J S (1993)
Pharmacologic studies of itraconazole (IZ), a triazole antifungal, indicated unexplained differences between bioassay and chromatographic determinations and large variations in steady-state blood concentrations. We show that concentrations of a hydroxylated metabolite, hydroxyitraconazole (HIZ), are approximately twofold higher than IZ over a range of concentrations. Though HIZ and IZ appear equipotent against selected pathogens, HIZ is two to three times more active against a commonly used bioassay fungus but minimally affects IZ activity. Hence, HIZ probably contributes importantly to the therapeutic activity attributed to IZ and contributes approximately four to six times the activity of IZ in bioassays, explaining discrepancies observed between assay methods.